'The right path of equality': supporting high school students with autism who type to communicate. Issue 4 (2nd April 2016) - Woodfield, Casey; Ashby, Christine
Abstract : The inclusion of students who type to communicate has been researched and strategies to accommodate such students have been recommended, but little information has been gathered about the students' perspectives and daily school lives. This study utilises classroom observations and qualitative interviewing to explore the experiences of three high school students who type to communicate and the systems in place to support them. The study privileges and focuses on the ways that their school personnel honour the voices of those students as contributors to the construction of the spaces they enter and ways in which their active participation is supported.